The impact of digitalisation on the business operations of tourism companies - Jagodič, Gregor (Mednarodno inovativno poslovanje, 2025)
Purpose of the article –this article examines how digitalisation influences business operations in tourism companies across multiple dimensions, including marketing, reservation management, customer communication, and internal information systems. The study addresses gaps in understanding the comprehensive implementation of digital technologies in tourism.Research methodology –The research employed a qualitative approach through semi-structured interviews with eight tourism industry experts holding positions as hotel managers, sales and reservations managers, and marketing managers. Data was collected in January 2025 and analysed using thematic coding based on the theoretical framework.Findings –reveal that digitalisation significantly enhances operational efficiency, enables precise audience targeting, facilitates personalised customer communication, and improves strategic decision-making through data analytics. While social media and online booking platforms are widely adopted, advanced technologies like Artificial Intelligence (AI) and Virtual Reality (VR) face implementation barriers due to cost constraints and knowledge gaps.
Keywords: digital marketing; digitalisation; digitalizacija; digitalni marketing; inovacije v turizmu; reservation systems; rezervacijski sistemi; tourism innovation; tourism management; Turisti; Turizem; upravljanje v turizmu